A Giant Hydatid Cyst at Right Frontoparietal Region: A Rare Case Report (Bangladesh Journal of Neuroscience, 2015)
Background: Hydatid cyst is a parasitic disease which can affect the central nervous system.Objective: The purpose of the study is to reveal the clinical findings and the effect of giant the intracranial hydatid cyst at frontoparietal region, which is a rare finding.Results: A patients with right frontoparietal hydatid cyst was admitted in our hospital with history of headache, seizure and left upper limb weakness. We operated the patient and postoperatively developed hydrocephalous and pseudocyst at the site of operation. Cystoperitoneal shunt was done. The patient was medically treated by albendazole. The patient cured postoperatively.Conclusion: Patients with intracranial hydatid cyst can be treated surgically and with albendazole.Bangladesh Journal of Neuroscience 2015; Vol. 31 (2): 116-120